Physically Activated Agricultural Waste Biochars for Production of Pollutant Adsorbents - Despina Vamvuka; EvangelosMachairas; Stelios Sfakiotakis; Olga Pantelaki (Journal of Chemical Engineering Research Updates, 2020)
Various nut residues from agricultural production were investigated for their potential to be used as active carbons. Raw materials were pyrolyzed in a fixed bed unit and subsequently gasified by steam or carbon dioxide at different temperatures and duration of heat treatment. Biochars were characterized by physical and chemical analyses with respect to temperature and gasifying agents. Organic and mineral matter, elemental composition, structural characteristics, and surface functional groups were determined. Activation by steam presented a higher reactivity than carbon dioxide, reduced the yield of biochars, consumed more oxygen organic functional groups, favoured pore enlargement at high temperature, and increased the specific surface area (maximum 1257 m2/g) of pyrolyzed materials by 1.4 to 3.8 fold. Activation by carbon dioxide disrupted the hydrogen char structure, favoured microporosity, and increased the specific surface area (maximum 637 m2/g) of pyrolyzed materials by 1.8 to 3 fold. Gasified biochars at a high temperature were highly carbonized and exhibited aromatic structures, especially under steam activation.